"And who was left to deal with it? The police": reflecting on permanent, low-intensity austerity in Memphis - Tulumello, Simone (2018)
In this essay, I elaborate two ideas on austerity and its politics. First, though austerity is often understood as a “response” to any number of (economic, political…) crises, there are places where it is a permanent reality. And, second, despite being often equaled to state roll-back, austerity is rather a process by which state action is restructured with specific political goals. In contrast with Jeremy Peck’s extreme “austerity urbanism”, I discuss the use of austerity as a long-term entrenched mechanism of urban government, which I shall define “low-intensity” austerity. To do so, I focus on the case of Memphis, and more generally of the South of the US, which not only are marginalized by mainstream explanations of neoliberalism and austerity, but offer paradigmatic exemplifications of the entrenchment of low-intensity austerity with the US institutional and political system. In particular, I shall focus on the role of urban security and crime control, their policies and politics, and their central role in the restructuring of US local policymaking.